(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The liquid limit of a soil is a fundamental index property that is routinely used in engineering practice to predict the behavior of cohesive soils. The Casagrande and fall cone test methods are the standard methods used to determine liquid limit. However, these methods require significant sample preparation, are time-intensive, and are subject to a range of errors dependent on the experimenter’s technique and experience. The study presented here investigates the feasibility of an alternative method for determining the liquid limit of soil. The nature of the definition of liquid limit suggests a relationship between viscosity, a mechanical fluid property, and the liquid limit. Accordingly, this study investigates the relationship between liquid limit, determined by Casagrande method, and the Marsh Funnel viscosity. The Marsh Funnel viscosity test produces an indicator of absolute viscosity by observing the time required for a fluid to flow through a calibrated funnel. Four different types of soil were prepared at a range of successively decreasing moisture contents. The liquid limit of the material was taken as the moisture content at which the Marsh Funnel viscosity approached infinity (stopped flowing). This value was then compared to the liquid limit determined using the Casagrande method in order to make preliminary conclusions regarding the suitability of using the Marsh Funnel test as an alternative method to determine liquid limit.